0D to 1D Switching of Hybrid Polyoxometalate Assemblies at the Nanoscale by Using Molecular Control. Issue 10 (5th August 2013) - Chen, Wei; Ma, Dui; Yan, Jun; Boyd, Thomas; Cronin, Leroy; Long, De‐Liang; Song, Yu‐Fei
<x xml:space="preserve">Abstract</x> Watered down: Polyoxometalate (POM) hybrids based on [C16H36N]4[SiW11O40(SiCH2CH2CH2NH2⋅HCl)2] covalently functionalized with different lengths of alkyl chains (n=0, 5, or 10) terminated with azobenzene moieties have been successfully prepared (see picture). The assembly behavior of these POMs can be affected by hydrophobic and π–π interactions by finely tuning the lengths of the alkyl chains in different ratios of CH3CN/H2O.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>